Avro data - Cutting, Doug (O'Reilly Media, 2011)
"Apache Avro provides an expressive, efficient standard for representing large data sets. Avro data is programming-language neutral and MapReduce-friendly. Hopefully it can replace gzipped CSV-like formats as a dominant format for data."--Resource description page.